Influence of operating temperature on efficiency Chinese made silicon solar cells - Zaitsev, R.; Kirichenko, M. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2017)
Currently, as a result of increasing the efficiency of industrialdesigns monocrystalline silicon solar cells to 17-18% with asignificant decrease in their cost Chinese manufacturers were thelargest importers of photovoltaic products in the world. Much ofenterprises engaged in the industrial production of photovoltaicmodules as initial photovoltaic cells use solar cells in China. Inaddition to the market segment, most imported PV modulesproducts also occupy Chinese manufacturers. However, in theoperation of such devices according to the size of only a fractionof the efficiency of solar energy used to generate electricity.Most of the solar radiation is converted to heat in the devicestructures. This increases the operating temperature of photovoltaiccells, in accordance reduces their effectiveness.Based on the above, the purpose of this work was to studythe effect of temperature on the efficiency of photovoltaic processesin the industrial design of photovoltaic cells in China.СОНЯЧНА ЕНЕРГЕТИКА ISSN 1819-8058Відновлювана енергетика. 2017. № 3 41The influence of operating temperature on the efficiencysilicon photovoltaic Chinese production showed that with increasingoperating temperature reduction efficiency is 0,07%/°C, which is significantly higher than in device structures ofEuropean and domestic production due to unconventional andreduce short-circuit current density.The method of computer modeling of quantitative exposurelight diode characteristics on efficiency have been shown thatlowering efficiency silicon photovoltaic Chinese production isdue not only to the traditional reduction diode saturation currentdensity but also decrease in shunt resistance.Identified temperature dependence of efficiency demonstratesthe feasibility of using Chinese-made photovoltaic cells inthe construction of photovoltaic thermal plants, which togetherwith the heat pump is part of a combined hot water, heating andair conditioning.